"Isogeometric thermal postbuckling analysis of porous FGM quasi-3D nanoplates having cutouts with different shapes based upon surface stress elasticity" [Composite Structures 262 (2021) 113604]. (15th October 2021) - Zenkour, Ashraf M.
Abstract: In this contribution, as comments to the paper in Composite Structures 262 (2021) 113604, will be shown that one of the shape function is not correctly described. This shape function is recorded during presenting the displacement field, and it was wrongly used as a part of the transverse shear strains. The correct form of the shape function is explained more deeply in the literature.